Does the new vascular management of acute limb ischemia have effective results with lower treatment costs - Haris Vukas; Samra Kadić-Vukas; Senad Dervišević; Adis Salihbegović; Haris Vranić; Muhamed Djedović; Amel Hadžimehmedagić; Dragan Totić (Medicinski glasnik, 2019)
Aim: To compare hospital costs of acute limb ischemia treatment in two periods of time and to show evidence of long-term repercussions on reducing costs during successful treatment. Methods: Retrospective analysis of data obtained from 100 patients' medical history in the period 2000-2016 at the Clinic of Vascular Surgery Sarajevo: group A-60 patients with acute limb ischemia in the period 2005-2016 and group B-40 patients with acute limb ischemia (ALI) in the period 2000-2005. From 2000 to 2005 conservative treatment method was used, invasive diagnostic and surgical procedures were often delayed for a shorter or longer period of time. During the period from 2005 to 2016, the management model and safe practice included emergency diagnostic procedures, colour-Doppler, arteriography, emergency surgery (embolectomy by Fogharty and if necessary, vascular bypass). Results: Better health service for the patients with acute limb ischemia was offered in the period 2005-2016, which relied on proven medical treatment trends. The largest share of the total costs of each patient included costs of hospital bed with significant difference between the period 2005-2016 and 2000-2005, mean of 1398.71 KM and 2480.45KM, respectively (p <0.0001), indicating rationalization of time that patients spend at the Vascular Clinic. Conclusion: This trend of money/fund savings is an example of good practice, effectiveness and efficiency in the treatment of ALI and as such was used in patients with other vascular diseases.
Keywords: acute limb ischemia; cost; embolectomy by Fogharty; vascular